DEVELOPMENT OF TEXTBOOKS FOR EXPORT-IMPORT COURSES BASED ON PROJECT BASE LEARNING APPROACH - Siti Sri Wulandari; Triesninda Pahlevi; Lifa Farida Panduwinata; Durinda Puspasari; Jaka Nugraha (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2023)
Textbooks are an important part of the learning process which are written with a specific purpose and regulated by the Ministry of Research, Technology and Higher Education. Textbooks are useful for supporting the learning process in accordance with the lecture curriculum in the Office Administration Education S1 study program, Faculty of Economics and Business, UNESA, especially in the Export Import subject. The purpose of this study was to determine the feasibility of project-based learning textbooks for export-import subjects, to determine the practicality of project-based learning textbooks for export-import subjects, to determine the effectiveness of project-based learning textbooks for export-import subjects. This research method uses 4-D. Data collection techniques were carried out using validation techniques and questionnaires with instruments in the form of language validation sheets, graphic validation sheets, material validation sheets and student response questionnaires. Technology Readiness Stage or Technology Readiness Level (TRL) is 3. The technology measured in this study is textbooks with ISBNs with the TRL indicator category being the Social Humanities and Education sector. The conclusion from this study is that the process of developing export-import textbooks uses the Research and Development model, the feasibility results of export-import textbooks are obtained from the validation of a team of experts namely material experts, linguists, and media experts who are included in the very feasible category, the practicality of export textbooks -import the results of student responses in the very feasible category, the average student learning outcomes in using this textbook increased by 9.56.